Application of stochastic logistic laws and their density mixtures to the growth analysis - Rupšys, Petras; Raškinienė, Danutė (Lietuvos matematikos rinkinys, 2023)
The processes of growth play an important role in different fields of science, such as ecology, economics, finance etc. In applications the averaged trend kinetics is represented by means of one of the types of logistic forms (Verhulst, Gompertz, Mitscherlich, Richards et al.). The article deals with the numerical solutions of the Fokker–Plank equation.